v1 is a prime of the form p^2+p+1, where p is prime
(There exists v1)(P(p)-->(v1=p*P+P+0') )
it looks too simply, can i get a feedback thanks
This has to be a formula with one free variable v1.v1 is a prime of the form p^2+p+1, where p is prime
Here, on the other hand, the only free variable is p. Also, in p*P, it confuses p, which is a number, with P, which is apparently a unary predicate saying that its argument is prime.(There exists v1)(P(p)-->(v1=p*P+P+0') )
You need to say that (1) there exists some prime p, (2) v1 = p * p + p + 0' and (3) v1 is prime.
In addition, what happens when ∃p chooses a number that is not prime? Then the premise P(v1) ∧ P(p) is false and the formula is automatically true. The English phrase "there exists a p satisfying P such that..." is translated into "∃p (P(p) ∧ ...)", while "for all p satisfying P it is true that..." is translated into "∀p (P(p) → ...)".
P(v1) & Ep(P(p) & v1 = p^(2+p+1))
However, if the exponentiation symbol (^) is not a primitive of your language, then you have to define ^ from the rest of the primitives. That is not a simple matter. Godel first showed how to do it, using the Chinese remainder theorem. (There might be ways to do it without using the Chinese remainder theorem, but that's how it's done ordinarily).